The Role of The School Committee in Managing Facilities and Infrastructure in SMKN 1 Pangandaran - Dela Zahara; Ai Siska Silvia (CV Projurnal Mitra Publikasi, 2025)
This study aims to analyze the role of the school committee in the management of facilities and infrastructure at SMKN 1 Pangandaran, focusing on the procurement, maintenance, and disposal of educational facilities. The approach used is qualitative with a case study research design. Data were collected through interviews, observations, and documentation, and analyzed inductively. The results show that the school committee plays an active role in every stage of managing facilities and infrastructure, from planning to disposal. The committee's role includes four main functions: as an advisor, supporter, controller, and mediator between the school and the community. Although the committee has carried out its duties effectively, it still faces several challenges, such as limited land and funding. Nevertheless, the management of facilities and infrastructure at SMKN 1 Pangandaran shows satisfactory results with routine maintenance and procurement based on needs and priorities. This study concludes that the role of the school committee is crucial in ensuring the smooth operation and sustainability of the quality of facilities and infrastructure, which in turn supports the quality of education at the school.